2007
DOI: 10.1136/pgmj.2006.049742
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery bypass surgery in elderly people

Abstract: An increasing number of elderly individuals are now undergoing coronary artery bypass surgery. Elderly patients, compared with patients of a younger age group, present for surgery with a greater burden of risk factors and reduced functional levels. Short-term outcomes are hence poorer in them. But symptom relief occurs in most survivors and is accompanied by excellent rates of long-term survival and a good quality of life. Therefore, an individualised risk-benefit profile must be carefully constructed by clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 37 publications
1
77
0
6
Order By: Relevance
“…Rev Bras Cir Cardiovasc 2011; 26.1: [21][22][23][24][25][26] In this study, it was also described that the mortality chance during hospitalization of an 80-year-old patient, in multivariate analysis, was 3.25 times the chance of a 50-year-old patient.…”
Section: Pivatto Junior F Et Al -Long-term Survival Of Octogenarian mentioning
confidence: 88%
See 2 more Smart Citations
“…Rev Bras Cir Cardiovasc 2011; 26.1: [21][22][23][24][25][26] In this study, it was also described that the mortality chance during hospitalization of an 80-year-old patient, in multivariate analysis, was 3.25 times the chance of a 50-year-old patient.…”
Section: Pivatto Junior F Et Al -Long-term Survival Of Octogenarian mentioning
confidence: 88%
“…Salomon et al [19] demonstrated in a 6-year follow-up period a percentage of angina-free survival of 77% and Mullany et al [20], in a 5-year follow-up period with 159 patients over 80 years old, observed a percentage of 79%. The excellent long-term survival in elderly patients after the completion of the CABG may be accompanied by a satisfactory quality of life in most patients [21].…”
Section: Pivatto Junior F Et Al -Long-term Survival Of Octogenarian mentioning
confidence: 99%
See 1 more Smart Citation
“…28 In the case of CABG, intraoperative or postoperative MI, low cardiac output syndrome, stroke, gastrointestinal complications, wound infection and renal failure occur more frequently in elderly patients after cardiac surgery and predict adverse outcomes. 29 Accordingly, aggressive revascularization in elderly patients with CTO should be carefully determined under consideration of lesion characteristics, physiological age and physical activity.…”
Section: Disclosures/competing Interests/grant Supportmentioning
confidence: 99%
“…Coronary artery bypass grafting (CABG) is the gold standard intervention in patients with complex multivessel disease [3]. In the UK, there are about 25,000 CABG operations performed annually [4] and the majority of these operations is carried out on patients over 70 years of age [5]. Demand for CABG is likely to increase considerably in the future as a result of rapidly ageing populations [6] and increased expectations of patients and surgeons to expand their indications for surgery.…”
Section: Coronary Artery Bypass Grafting (Cabg)mentioning
confidence: 99%